The Effects of Intermittent Pneumatic Compression during Cesarean Delivery on Fibrinolysis - Reddick, Keisha L. B.; Smrtka, Michael P.; Grotegut, Chad A.; James, Andra H.; Brancazio, Leo R.; Swamy, Geeta K. (American Journal of Perinatology, 2014)
Objective Pregnancy is associated with increased risk for thromboembolic events. Intermittent pneumatic compression (IPC) devices are the method of thromboprophylaxis in a nonpregnant population. The aim of this study was to examine the effects of IPC on markers of fibrinolysis during cesarean delivery.Study Design We conducted a randomized controlled trial from April 2009 to March 2010 of women undergoing scheduled elective cesarean delivery. Forty-nine women were randomized to IPCs or usual care. All participants had three blood samples obtained: (1) baseline, (2) 1 hour after randomization, and (3) 30 minutes after cesarean delivery. Tissue-type plasminogen activator (tPA), urokinase-type plasminogen activator (uPA), thrombin-antithrombin complex (TAT), plasminogen activator inhibitor-1 (PAI-1), and plasminogen activator inhibitor-2 (PAI-2) levels were analyzed in each sample using an enzyme-linked immunosorbent assay. Statistical analysis was performed using repeated measures two-way analysis of variance with α = 0.05.Results There was a time-dependent change in tPA, uPA, and PAI-1 levels following delivery but no difference in TAT and PAI-2 levels with time. There were no differences between women randomized to IPCs or usual care.Conclusion Markers of fibrinolysis were not significantly altered by IPCs in this study of low-risk pregnant women. Further research regarding the mechanism and efficacy of IPCs in pregnant women is warranted.
Keywords: fibrinolysis; intermittent pneumatic compression; cesarean